Annual Report on Evaluation 2015 - United Nations Development Programme (United Nations, 2016)
The annual report on evaluation for 2015 assesses the progress made by the Independent Evaluation Office of United Nations Development Programme (UNDP), programme and policy units at UNDP headquarters, UNDP country offices and the evaluation units of the associated funds and programmes in fulfilling the evaluation function outlined in the UNDP evaluation policy. The report also presents key findings and lessons learned from independent evaluations conducted by the Independent Evaluation Office in 2015. It also sets out the programmes of work for 2016-2017 for the Independent Evaluation Office of UNDP.